A 3D Most Vulnerable Path Search Method for Physical Protection Systems Based on the EASI Model - Aiguo Li; Yanfeng Deng (IEEE Access)
Physical Protection System (PPS) is a crucial system for critical infrastructure to protect its vital information, and it is essential to analyze the vulnerability of PPS. Established methods for PPS vulnerability analysis mainly focus on one- and two-dimensional environments. However, the air and underwater threats are increasing, and more effective methods are needed to deal with these new threats than the existing methods. The security of the physical protection system in three-dimensional space needs to be analyzed. The most vulnerable path search is a critical link in the security assessment of the physical protection system, so this paper proposes a three-dimensional physical protection system based on the Estimate of Adversary Sequence Interruption (EASI) model of the most vulnerable path search method. A three-dimensional facility model is established, and the algorithm’s search points are reduced based on existing methods. The search efficiency is improved by restricting the intermediate points and the angle between the start and target points and improving the heuristic function. The improved algorithms are simulated and compared, and the results show that the paths generated by the improved algorithms are more reasonable, and the algorithms consume less time and have shorter path lengths.